2022
DOI: 10.1177/2473011421s00220
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin Gene-Related Peptide in Charcot Foot Neuroarthropathy

Abstract: Category: Basic Sciences/Biologics; Diabetes Introduction/Purpose: Charcot neuroarthropathy (CNA) is a destructive joint condition secondary to neuropathic deficiency. For more than a century, the pathogenesis of CNA has been interpreted as unprotected injury and/or uncontrollable inflammation in a neuropathic joint, with little understanding its cellular and molecular pathology. Histologically, a hallmark of CNA is bone and cartilage fragments engulfed by hyperplastic synovium. Synovium is richly innervated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Pasquier et al noted an altered expression profile of circulating miRNAs, and Guo et al suggested that calcitonin gene-related peptide (CGRP) may also play an important role due to its ability to stimulate collagen degradation in vivo because higher rates of CGRP in the synovium of patients with CN were discovered. [17][18][19] Lastly, there are alternative causes of Charcot other than diabetes, such as syphilis, alcoholism, B12 deficiency, and idiopathic.…”
Section: Review Background and Pathophysiologymentioning
confidence: 99%
“…Pasquier et al noted an altered expression profile of circulating miRNAs, and Guo et al suggested that calcitonin gene-related peptide (CGRP) may also play an important role due to its ability to stimulate collagen degradation in vivo because higher rates of CGRP in the synovium of patients with CN were discovered. [17][18][19] Lastly, there are alternative causes of Charcot other than diabetes, such as syphilis, alcoholism, B12 deficiency, and idiopathic.…”
Section: Review Background and Pathophysiologymentioning
confidence: 99%